Isolated Intraorbital Frontosphenoidal Synostosis. Issue 1 (January 2018) - Mittermiller, Paul A.; Yeom, Kristen W.; Menard, Robert M.
Abstract : Abstract: Unilateral anterior plagiocephaly is most commonly the result of deformational plagiocephaly or unilateral coronal synostosis, a premature fusion of the frontoparietal suture. However, other sutures within the coronal ring have been implicated in producing anterior cranial asymmetries. These fusions can occur in isolation or in concert with adjacent sutures. The frontosphenoidal suture is one such suture within the coronal ring that has been involved both concomitantly with and independently of frontoparietal suture fusion. Although isolated frontosphenoidal synostosis has been presented previously in the literature, these reports include patients with fusion of the extraorbital portion of the frontosphenoidal suture. This clinical report presents the first clearly documented patient of isolated frontosphenoidal synostosis that occurs entirely within the intraorbital region. The patient presented to Plastic Surgery Clinic at 3 months of age with left frontal flattening, supraorbital rim retrusion, and temporal bulging that was noted soon after birth. Computed tomography analysis revealed an isolated fusion of the greater and lesser wings of the sphenoid bone to the frontal bone on the left side. The patient had no family history of cranial anomalies and genetic testing was negative for mutations. The infant was treated with a cranial orthotic for 3 months, underwent open fronto-orbital advancement and cranial vault remodeling at 6 months, and continued wearing a cranial orthotic for another 4.5 months. Following surgical and orthotic treatment, the patient achieved a satisfactory result.